Protein fractionation and shotgun proteomics analysis of enriched bacterial cultures shed new light on the enzymatically catalyzed degradation of acesulfame. (15th February 2023) - Castronovo, Sandro; Helmholz, Lissa; Wolff, David; Poulsen, Jan Struckmann; Nielsen, Jeppe Lund; Ternes, Thomas A.; Schmidt, Torsten C.; Wick, Arne
Highlights: Ensifer adhaerens and a Chelatococcus sp. enriched using acesulfame as C-source. Enzymatically catalyzed degradation of the artificial sweetener in lysates. Protein fractionation via two-dimensional fast protein liquid chromatography. Protein expression profiling of acesulfame degraders via shotgun proteomics. Identification of enzyme candidates likely involved in the transformation pathway. Abstract: The removal of organic micropollutants in municipal wastewater treatment is an extensively studied field of research, but the underlying enzymatic processes have only been elucidated to a small extent so far. In order to shed more light on the enzymatic degradation of the artificial sweetener acesulfame (ACE) in this context, we enriched two bacterial taxa which were not yet described to be involved in the degradation of ACE, an unknown Chelatococcus species and Ensifer adhaerens, by incubating activated sludge in chemically defined media containing ACE as sole carbon source. Cell-free lysates were extracted, spiked with ACE and analyzed via target LC-MS/MS, demonstrating for the first time enzymatically catalyzed ACE degradation outside of living cells. Fractionation of the lysate via two-dimensional fast protein liquid chromatography (FPLC) succeeded in a partial separation of the enzymes catalyzing the initial transformation reaction of ACE from those catalyzing the further transformation pathway. Thereby, an accumulation of the intermediate transformation product acetoacetamide-n-sulfonic acid (ANSA) in the ACE-degrading fractions was achieved, providing first quantitative evidence that the cleavage of the sulfuric ester moiety of ACE is the initial transformation step. The metaproteome of the enrichments was analyzed in the FPLC fractions and in the unfractionated lysate, using shotgun proteomics via UHPLC-HRMS/MS and label-free quantification. The comparison of protein abundances in the FPLC fractions to the corresponding ACE degradation rates revealed a metallo-β-lactamase fold metallo-hydrolase as most probable candidate for the enzyme catalyzing the initial transformation from ACE to ANSA. This enzyme was by far the most abundant of all detected proteins and amounted to a relative protein abundance of 91% in the most active fraction after the second fractionation step. Moreover, the analysis of the unfractionated lysate resulted in a list of further proteins possibly involved in the transformation of ACE, most striking a highly abundant amidase likely catalyzing the further transformation of ANSA, and an ABC transporter substrate-binding protein that may be involved in the uptake of ACE into the cell. Graphical abstract: Image, graphical abstract